2009
DOI: 10.1128/jb.01260-08
|View full text |Cite
|
Sign up to set email alerts
|

Chenodeoxycholate Is an Inhibitor of Clostridium difficile Spore Germination

Abstract: Some cholate derivatives that are normal components of bile can act with glycine to induce the germination of Clostridium difficile spores, but at least one bile component, chenodeoxycholate, does not induce germination. Here we show that chenodeoxycholate inhibits the germination of C. difficile spores in response to cholate and taurocholate.The anaerobic human pathogen Clostridium difficile must be in the spore form to survive for extended periods of time outside the colonic environment (6). Spores are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
182
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(193 citation statements)
references
References 18 publications
3
182
1
Order By: Relevance
“…Indeed, recent work has shown that C. difficile spores recognize taurocholate (a bile salt) and glycine (an amino acid) as germinants (53). Furthermore, chenodeoxycholate was shown to be a naturally occurring inhibitor of C. difficile spore germination (54). Work from our laboratory has shown cooperative binding of both taurocholate and glycine, suggesting the presence of unidentified receptors for both germinants (39).…”
mentioning
confidence: 92%
“…Indeed, recent work has shown that C. difficile spores recognize taurocholate (a bile salt) and glycine (an amino acid) as germinants (53). Furthermore, chenodeoxycholate was shown to be a naturally occurring inhibitor of C. difficile spore germination (54). Work from our laboratory has shown cooperative binding of both taurocholate and glycine, suggesting the presence of unidentified receptors for both germinants (39).…”
mentioning
confidence: 92%
“…In vitro studies indicate that germination and outgrowth into the vegetative form depends on the presence of specific primary bile acids, such as taurocholate (20,21). Conversely, other secondary bile acids, such as chenodeoxycholate, inhibit the germination of C. difficile spores (22). Microbes within the gastrointestinal tract play a key role in the metabolism of bile acids (23), and it is hypothesized that the modulation of the microbiota community can impact metabolite availability.…”
Section: Pathogenesis: Spore Exposure and Disease Developmentmentioning
confidence: 99%
“…126 Based on their studies on the differential growth of C. difficile on various bile salts, Sorg & Sonnenshein propose yet another mechanism by which the native flora may impede CDI. 127,128 Their hypothesis is that native flora convert cholate to deoxycholate, a compound that is toxic to vegetative C. difficile and inhibits germination of C. difficile spores.…”
Section: Colonization Resistancementioning
confidence: 99%